An experimental and a numerical investigation of a high pressure die casting aluminium alloy - Boydak, Özlem. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2007., 2007)
In the present study, a computer simulation of a high pressure die casting of aluminium alloy was performed using a sophisticated commercial software called Magmasoft and, then its results were compared with the real castings of the same aluminium alloy. The commercial aluminium alloy was Etial 150 (AlSi12Cu) that was used for a flange which was a washing machine part. Mould filling, solidification, temperature distribution, temperature profile, air entrapment, and velocity of the liquid metal during die casting was investigated using the modelling. After this numerical model, an experimental study was carried out. The actual mould was manufactured and the alloy above was cast in the high pressure die cast machine. Comparing the experimental results with theoretical model, the microstructure and mechanical properties of the casting was discussed with the help of tensile and hardness testing specimens, and microstructure of these specimens. Additionally, Etial 150 alloy was squeeze cast in the Material Laboratory of Mechanical Engineering Department of Boğaziçi University. Four specimens were melted at 700°C, and they were squeezed in the squeeze casting set-up under 100 MPa presssure. The temperature of the die and punch was 300°C for three castings and it was 400°C for the last casting for comparison. Moreover, six specimens of Etial 150 alloy were unsqueezely cast to the same die at 400°C. Furthermore, six more specimens of Etial 150 alloy were also unsqueezely cast to the 20°C die. All these specimens were analyzed with tensile testing, hardness testing, and microstructural investigation. Finally, all of the results were interpreted.
Keywords: Aluminum alloys.